Emergency Room Medical Record Modification to Optimize Patient Education at X Hospital - Hariyanto, Engelbert; Prastowo, Wening; Zuhriyah, Lilik (Fakultas Kedokteran Universitas Brawijaya, 2022)
Regularly delivering information to patients and their families becomes a challenge for medical personnel in the Emergency Room (ER). Patients, or their families, often do not remember that education about their illness has been delivered. It can also happen because family members who took the patients into the emergency room differed from those who received the education. This situation can lead to misunderstandings, especially if there are legal problems in the future. This study aimed to find the priority problem in the hospital, the root of the problem, and solutions to optimize patient education in the ER. The methods used in the problem-finding were interviews, Focus Group Discussions (FGD), and USG (Urgency, Seriousness, and Growth) scoring. The solution selection method used FGD, fishbone analysis, 5-whys table, and CARL (Capability, Accessible, Readiness, and Leverage) scoring. The problem found was the lack of optimal patient education in the ER. The priority of the root of the problem found was no written documentation in the patient's medical record regarding providing education to patients or families. The chosen solution was to modify the ER medical record by including a checklist of educational points and a column for patients or families to sign. Further research is needed to prove the effectiveness of this medical record modification in optimizing education in the ER.